KONSEP KEBAHAGIAAN DALAM TASAWUF MODERN HAMKA - Arrasyid, Arrasyid (UIN Sunan Kalijaga Yogyakarta, 2019)
Happiness is an eternal concept that will always keep being up to date which means the concept of happiness will never be ended for discussion. Starting from ancient times, people today, and people in the future always want the same thing as happiness. The concept of happiness is not something new for both the world of Sufism and philosophy, therefore the concept of happiness experiences the dynamic development of the concept. Hamka is one of the scholars in Indonesia who discusses the concept of happiness, but Hamka has its own characteristics in explaining happiness. According to Hamka, happiness actually exists in every human being, happiness can be achieved from inside, not from outside, happiness that comes from outside of ourself is only as a complement to happiness inside, happiness can be achieved if humans always hone and develop tools which can be used to achieve happiness and these tools are religion, reason, and mind. These three things have a relationship with each other, if humans are able to develop these three things then humans can achieve happiness in their lives. In achieving happiness, these three things can be applied by using several methods namely zuhud, sincere, qana’ah and tawakal. The background of this research will explain the concept of happiness in the modern mysticism of Hamka. This research is a library research, and to make it more functional and useful, this paper will be equipped by a description method, interpretation and analysis of data in detail for each problem raised, therefore it can obtain a comprehensive understanding.